Spindle cell tumor presenting as RIF mass - Gowtham, Thakut; Murchite, Sheetal Ashok; Gaikwad, Vaishali Vinayak; Chougale, Abhay D.; Ranjan, Rakesh Kumar; Thimmegowda, Vishwas (International Surgery Journal, 2019)
Spindle cell sarcoma is a rare tumor that arises most commonly from the peripheral and deep soft tissues. It usually occurs in the extremities but rarely present as a large abdominal mass, and in this case it was a recurrent tumor involving whole of rectus muscle on right side. We report the case of a 42 year old male who presented with abdominal swelling and distention. CT scan showed a mass occupying the whole of the abdomen and pelvis. Exploration of abdomen revealed a hard mass about 13×10×11 cm in size. Complete excision was done, the huge defect was closed by transposition of left side rectus abdominus muscle with prolene mesh, which was a challenging task in this case. On histopathology and immunochemistry a high grade spindle cell carcinoma was confirmed.